Amyand ‘S Hernia: Case Report and Review of the Bibliography - ATTOLOU, SÈTONDJI GILLES ROGER (My University, 2019)
Amyand’s hernia (AH) is an extremely rare presentation of right inguinal hernia characterized by the presence of the vermiform appendix, either inflamed or normal, in an inguinal hernia sac. The reported incidence is approximately 1% of all inguinal hernia cases. Treatment is not well codified and remains controversial about whether or not to perform an appendectomy when the appendix is normal, and about usage of mesh in cases of appendectomy. We report our experience with five cases of Amyand’ S hernia. All patients were male, aged 31, 65, 69, 22 and 29 years old. The diagnosis was a per-operative surprise in all cases. Two patients presented with strangulated hernia without appendicular complication. Treatment included systematic appendectomy followed by inguinal hernia repair using modified Shouldice technique. All patients recovered well without any septic complication or hernia recurrence. Postoperative courses were uneventful. Even in the absence of appendicitis, appendectomy followed by anatomic inguinal hernia repair can be performed in young males without morbidity
Keywords: Amyand's hernia; appendix; inguinal hernia; herniorraphy; appendectomy